2006
DOI: 10.1002/ajmg.a.31117
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in Brooks–Wisniewski–Brown syndrome

Abstract: Brooks, Wisniewski, and Brown described a familial presentation of severe developmental retardation, speech delay, static encephalopathy with atrophic hydrocephalus, microcephaly, progressive spastic diplegia, a characteristic facial appearance, optic atrophy, and growth retardation associated with hypoplastic corpus callosum in one of the patients. The authors postulated a distinct X-linked mental retardation syndrome. Later on a similar phenotype was observed in three male siblings with an early lethal outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…In addition, there were clinical discrepancies between the affected probands and the BWB patients described in the literature. The boys described by Brooks et al presented with spastic diplegia, optic and cerebellar atrophy, and entropion, which were not noted in our cases; the majority of patients reported by Morava exhibited regression, seizures, and corpus callosum hypogenesis that were not present in the patients described in the current study. Given that BWB syndrome is an extremely rare disorder and exhibits a high degree of clinical heterogeneity, it is possible that BWB could be genetically heterogeneous and that the phenotype of our patients represents a BWB‐like disorder, caused by mutation in a gene other than HUWE1 .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In addition, there were clinical discrepancies between the affected probands and the BWB patients described in the literature. The boys described by Brooks et al presented with spastic diplegia, optic and cerebellar atrophy, and entropion, which were not noted in our cases; the majority of patients reported by Morava exhibited regression, seizures, and corpus callosum hypogenesis that were not present in the patients described in the current study. Given that BWB syndrome is an extremely rare disorder and exhibits a high degree of clinical heterogeneity, it is possible that BWB could be genetically heterogeneous and that the phenotype of our patients represents a BWB‐like disorder, caused by mutation in a gene other than HUWE1 .…”
Section: Discussioncontrasting
confidence: 56%
“…18 To date, there is no evidence of HS6ST2 involvement in Mendelian diseases. [19][20][21][22] ID, speech delay, and severe myopia in a context of mild dysmorphia were the specific key features supporting the similarity. Moreover, the three BWB patients described by Morava et al 21 presented with increased blood lactate values in infancy, similar to the affected twins.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It has been reported that mitochondrial function is essential for normal growth in pulmonary epithelial-like cells in culture (9). Compromised mitochondrial oxidative phosphorylation has been implicated in pathogenesis of genetic diseases presenting with developmental and growth restriction of different organs (10). Clearly, well-functioning mitochondria are needed to convert nutritional substrates into energy to maintain growth and development.…”
mentioning
confidence: 99%
“…Castro-Gago et al 8 carried out an analysis of muscle biopsies and described light microscopic morphology and ultrastructural alterations typical of mitochondrial disorders, and low levels of complexes III and IV of the mitochondrial respiratory chain in congenital hydranencephalic-hydrocephalic syndrome. Morava et al 9 reported mitochondrial dysfunction in Brooks-Wisniewski-Brown syndrome with a significantly compromised of mitochondrial oxidative phosphorylation. These findings raised the possibility that at least some cases of congenital hydranencephalic-hydrocephalic syndrome may be due to alterations in the mitochondrial respiratory chain.…”
Section: Introductionmentioning
confidence: 99%